Numerical, wind-tunnel, and atmospheric evaluation of a turbulent ground-based inlet sampling system. Issue 6 (3rd June 2019) - Petersen, Ross C.; Hallar, Anna G.; McCubbin, Ian B.; Ogren, John A.; Andrews, Elisabeth; Lowenthal, Douglas; Gorder, Riley; Purcell, Rick; Sleeth, Darrah; Novosselov, Igor
Abstract: The use of inlets for transferring aerosols from the environment to instrumentation can introduce uncertainty in the measurement of aerosol properties. Aerosol loss during this process is a non-negligible issue that may bias the subsequent measurements. These loss mechanisms include aspiration at the inlet head and deposition/evaporation/condensation during transport through the sampling lines. Coarse-mode aerosol is significantly impacted by the aspiration and inertial loss mechanisms within an inlet system. This work uses wind tunnel experiments to investigate aerosol losses through the Storm Peak Laboratory's (SPL) new aerosol inlet system. The inlet is used extensively for both intensive field campaigns and long-term aerosol monitoring. The results of numerical simulations of the SPL aerosol inlet sampling efficiency are provided at several wind speeds, and experimental results demonstrate the system has a 50% cut off for the coarse-mode at an aerodynamic diameter of approximately 13 μm and wind speed of 0.5 m s −1 . This investigation will lead to improved accuracy of in situ aerosol measurements at SPL and this system can be replicated at other atmospheric stations. Copyright © 2019 American Association for Aerosol Research